2017
DOI: 10.1016/j.cell.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Oscillations in Liver Mass and Cell Size Accompany Ribosome Assembly Cycles

Abstract: Summary The liver plays a pivotal role in metabolism and xenobiotic detoxification, processes that must be particularly efficient when animals are active and feed. A major question is how the liver adapts to these diurnal changes in physiology. Here, we show that, in mice, liver mass, hepatocyte size, and protein levels follow a daily rhythm, whose amplitude depends on both feeding-fasting and light-dark cycles. Correlative evidence suggests that the daily oscillation in global protein accumulation depends on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
171
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(184 citation statements)
references
References 52 publications
13
171
0
Order By: Relevance
“…3A), which were associated with feeding and fasting rhythms (Gene Ontology analysis around the clock) (Methods). Indeed, ribosome biogenesis was up-regulated most strongly during the first 6 h of the feeding phase (from ZT12 to ZT18) (Jouffe et al 2013;Chauvin et al 2014), while insulin signaling was down-regulated during first 6 h of the fasting phase (from ZT0 to ZT6) (Ravnskjaer et al 2013), consistent with daily responses to nutrient fluctuations in liver (Sinturel et al 2017).…”
Section: Combinatorics Of Rhythmic Transcript Expression Across Tissusupporting
confidence: 50%
“…3A), which were associated with feeding and fasting rhythms (Gene Ontology analysis around the clock) (Methods). Indeed, ribosome biogenesis was up-regulated most strongly during the first 6 h of the feeding phase (from ZT12 to ZT18) (Jouffe et al 2013;Chauvin et al 2014), while insulin signaling was down-regulated during first 6 h of the fasting phase (from ZT0 to ZT6) (Ravnskjaer et al 2013), consistent with daily responses to nutrient fluctuations in liver (Sinturel et al 2017).…”
Section: Combinatorics Of Rhythmic Transcript Expression Across Tissusupporting
confidence: 50%
“…A recent publication from the lab of Ueli Schibler showed that daily changes in actin dynamics in liver of mice are accompanied by pronounced size oscillations of mouse hepatocytes. (3) In a follow-up publication from the same lab published recently in Cell, Sinturel et al (4) demonstrated that these size changes are primarily regulated by feeding time.…”
mentioning
confidence: 99%
“…Furthermore, a large body of work shows that hepatic cell size changes induced by hormones or osmotic gradients can have many pleiotropic effects on organ function, among others an increase in cell volume which inhibits proteolysis and stimulates global protein translation in liver cells, (5) effectively resulting in the same positive correlation between cell size and protein mass as in the present study. (4) At this point, however, we cannot exclude the possible involvement of other cellular mechanisms or molecular constituents in the process of hepatic cell size oscillations. It was recently reported that hepatic lipid composition exhibits feeding-dependent daily rhythms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance edema can increase the water concentration significantly [86]. Another possible confounder is the daily variations in liver hydration [87,88]. In humans a daily variation of 20 % has been observed by ultra-sound [88].…”
Section: Fat-referenced Mri and Pdffmentioning
confidence: 99%